Ende Diabetes Study: diabetes and its characteristics in rural area of East Nusa Tenggara (Medical Journal of Indonesia, 2013)
Background: There are only few studies about diabetes in rural area in Indonesia. Epidemiological study are needed to formulate health policy of disease management in specific area. The aim of this study was to find the prevalence of diabetes and knowledge of diabetes among the community in Nangapanda Village, Ende District, East Nusa Tenggara. Methods: A cross-sectional study “Ende Diabetes Study” was conducted in Nangapanda Village. This study use cluster random sampling method to a total number of 19756 residents in Nangapanda village. From the sampling frame of 1800 adult subjects who underwent screening with glucometer in 2008 and 2009, 125 subjects have been diagnosed as diabetes or impaired fasting glucose (IFG). All of the subjects who were diagnosed as diabetes or IFG from the previous screening and 218 subjects from control (normal subjects in the 2008 and 2009 screening) were included in the present study. Each subject underwent general anamnesis, nutritional interview, complete physical examinations, and laboratory test (blood and urine). The data were analyzed using SPSS 13.0. Ressult: There were 343 subjects in this study. The prevalence of diabetes in Nangapanda using blood glucose criteria (using fasting and post-glucose load values) was 2%; using post glucose load criteria, the prevalence of DM was 1.56%; while with HbA1c criteria, the prevalence was 2.83%. The prevalence of impaired glucose tolerance (IGT) was 2.2%, and IFG was 6.2%. A number of 71.1% Nangapanda residents have sufficient knowledge about diabetes. Conclusion: Prevalence of diabetes in Nangapanda (using fasting and post-glucose load criteria) was 2% and 1.56% (using post-glucose load values). As much as 71.1% of Nangapanda residents have sufficient knowledge about diabetes. (Med J Indones. 2013;22:30-8) Keywords: Diabetes mellitus, Ende Diabetes Study, prevalence, rural Indonesia